2017
DOI: 10.1039/c7cp02771k
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of galloyl catechin aggregates significantly modulates membrane mechanics in the absence of biochemical cues

Abstract: Physical interactions of four major green tea catechin derivatives with cell membrane models were systemically investigated. Catechins with the galloyl moiety caused the aggregation of small unilamellar vesicles and an increase in the surface pressure of lipid monolayers, while those without did not. Differential scanning calorimetry revealed that, in a low concentration regime (≤10 μM), catechin molecules are not significantly incorporated into the hydrophobic core of lipid membranes as substitutional impurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…Interestingly, EGCG inhibited both IFNR/JAK2/STAT1 and EGFR/Akt signaling pathways, suggesting that EGCG inhibits IFN-γ-IFNR and EGF-EGFR activation by inhibiting ligand-receptor binding [ 11 ]. The results are consistent with a recent report that EGCG increased the bending stiffness of artificial lipid membranes by adsorption of galloyl catechin aggregates to the lipid membrane surface [ 20 ]. We also reported that stiffening of cancer cell membranes with EGCG correlates well with inhibition of EMT, motility, and metastasis in lung cancer cells and B16-F10 mouse melanoma cells [ 11 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, EGCG inhibited both IFNR/JAK2/STAT1 and EGFR/Akt signaling pathways, suggesting that EGCG inhibits IFN-γ-IFNR and EGF-EGFR activation by inhibiting ligand-receptor binding [ 11 ]. The results are consistent with a recent report that EGCG increased the bending stiffness of artificial lipid membranes by adsorption of galloyl catechin aggregates to the lipid membrane surface [ 20 ]. We also reported that stiffening of cancer cell membranes with EGCG correlates well with inhibition of EMT, motility, and metastasis in lung cancer cells and B16-F10 mouse melanoma cells [ 11 , 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…The system reached its stability after 70 ns of MD simulation, as confirmed by RMSD values (Figure 5a), and showed a very similar stabilization In addition, the employement of EGCG concentrations above 0.5 mM had the effect to form large aggregates precipitating within the sample tube (data not shown). This appears to be in agreement with previous studies, in which emerged the propensity of EGCG to increase precipitation phenomena in the vesicle suspensions [48][49][50]; interestingly, the suspension mixed with C18-EGCG did not yield any precipitate.…”
Section: Structural Insight Of C18-egcg Inside Lipid Bilayer: In Silisupporting
confidence: 93%
“…Of note, polyphenols specifically reduced the adhesion of pluripotent cells but not other differentiated progeny, leading to an increased difference in adhesion kinetics ( Figure 4 D, left). The shape of F difference ( Figure 3 B) resembles that of the cholesterol-depleted membrane ( Figure S3 B, bottom), suggesting that polyphenols interact with membranes with fluidic lipids and cholesterol confirmed by model membrane experiments ( Figure 4 D, right) ( Hwang et al., 2003 , Karewicz et al., 2011 , Matsuzaki et al., 2017 , Neves et al., 2015 , Ogawa et al., 2016 , Sun et al., 2009 ).…”
Section: Resultsmentioning
confidence: 52%